STRATEGI KOMUNIKASI PEMASARAN DIGITAL UMKM ARVA INDONESIA DALAM MEMASARKAN PRODUK DAN MENARIK MINAT PELANGGAN MELALUI MEDIA BARU - Nur Muhammad Mahdi Ulil Azmi (2023)
The snack food and beverage industry is one of the UMKM (Micro, Small, and Medium Enterprises) sectors that continues to grow despite being affected by the Covid-19 pandemic. Arva Indonesia, as a UMKM engaged in the production of tempeh chips, operates in Yogyakarta. Based on information available on the internet and various aspects such as social media, website , e-commerce, and export levels, Arva Indonesia stands out among other UMKMs in the tempeh chips sector, making it interesting to examine how Arva Indonesia markets its products and attracts customers. The purpose of this research is to gain a deeper understanding of the digital marketing communication strategies employed by UMKMs in order to enhance trust and product marketing to attract consumers. This research adopts a qualitative research method with a case study approach, employing purposive sampling technique to select five informants, including two key informants from Arva Indonesia's internal brand and three supporting informants who are Arva Indonesia's customers with specific criteria. The SOSTAC theory is utilized to ascertain a systematic structure and guidance for planning, implementing, and analyzing Arva Indonesia's marketing strategies. The findings of this research reveal that Arva Indonesia utilizes various new media in digital marketing communication, with Instagram being the primary platform, while the website and e-commerce channels have yet to be fully optimized, and the use of YouTube is no longer active. Arva Indonesia has achieved success in the strategy and tactics stages of marketing communication by identifying the appropriate target audience and designing effective strategies. However, there is still a need to enhance implementation, particularly in leveraging the potential of their website